Karya Tari di Antara Pijak Patah Interpretasi Filosofi Bajanjang Naiak Batanggo Turun - Wulandari, Putry; Stevenson, Yan; Emri, Emri; Putra, Ariefin Alham Jaya (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work Di Antara Pijak Patah is grounded in the Minangkabau philosophy of Bajanjang Naiak Batanggo Turun, a life principle that emphasizes order, process, and ethical conduct in social life. This philosophy has long served as a foundation for shaping social etiquette within Minangkabau society, particularly in intergenerational relationships, both within the family and in broader social contexts. However, alongside rapid social change and technological advancement, these values have gradually shifted, especially among younger generations who tend to prioritize speed and instant achievement over meaningful processes. This condition has contributed to a decline in ethical awareness, manners, and mutual respect in everyday social interactions. These circumstances form the basis for the creation of this dance work as a medium of reflection and social critique on contemporary social realities. Di Antara Pijak Patah is realized as an abstract contemporary dance with a social theme. The creative process involves several stages, including data collection, observation, exploration, improvisation, structuring, and evaluation. Movement development focuses on the exploration of space, time, and energy, combined with symbolic bodily expressions and the use of a ladder as a prop to represent the moral journey of the younger generation. This metaphor illustrates the rise and fall of ethical values and the fragility of moral foundations when social norms are neglected. The work is performed by four female dancers and accompanied by live music, which serves to enhance the dramatic atmosphere and reinforce the overall structure of the performance. Through Di Antara Pijak Patah, the choreographer seeks to convey a moral message regarding the importance of social etiquette, respect for process, and ethical awareness as fundamental aspects of social life. This work is expected to function as a space for reflection for younger generations while also contributing to the development of contemporary dance creation rooted in local cultural values.